Synthesis and in vitro anti-HIV-1 evaluation of some N-arylsulfonyl-3-formylindoles (Brazilian Journal of Pharmaceutical Sciences, 2018)
As our ongoing work on research of anti-HIV-1 inhibitors, fifteen N-arylsulfonyl-3-formylindoles (3ao) were designed and prepared through two step synthetic route. Firstly, 3-formylindoles (2a-c) were synthesized via the Vilsmeier-Haack reaction. Subsequently, treatment of 2a-c with the appropriate arylsulfonyl chlorides led to the corresponding target compounds in excellent yields. All analogues were also preliminary evaluated in vitro for their inhibitory activity against HIV-1 replication. Among of all the reported analogues, three compounds 3c, 3g and 3i displayed significant anti-HIV-1 activity, with EC50 values of 9.57, 11.04 and 5.02 μM, and TI values of 31.89, 13.79 and 81.69, respectively. N-mnitrophenylsulfonyl-3-formylindole (3c) and N-m-nitrophenylsulfonyl-6-methyl-3-formylindole (3i) especially exhibited the best promising anti-HIV-1 activity. In addition, it demonstrated that insertion of a methyl group at the C-6 position of the indolyl ring and a nitro group at the meta position of the arylsulfonyl ring, as in compound 3i, resulted in both low cytotoxicity (CC50 = 410.41 μM) and good antiviral activity.